Release of clearing factor lipase by the perfused rat heart - D.S. Robinson; M.A. Jennings (Journal of Lipid Research, 1965)
Rat hearts perfused with heparin in McEwen-albumin solution by the Langendorff technique released clearing factor lipase into the perfusate. Clearing factor lipase activity in the perfusate was high in the first minute of perfusion with heparin. With hearts from fed animals it remained at a high level for 10–15 min before falling gradually. With hearts from fasted animals it fell more rapidly and reached a low level by 10–20 min after starting perfusion. Total activity in the perfusate was greater with hearts from fed, than with those from fasted rats. If heparin was withdrawn from the perfusion fluid no sudden change occurred in the pattern of enzyme release.After one hour's perfusion both fed and fasted hearts retained a considerable proportion of their original clearing factor lipase activity although enzyme in the perfusate had fallen to a low level by this time.The enzyme content of unperfused hearts was higher in fed than in fasted rats.